ANALISIS TINGKAT KEKRITISAN LAHAN DI SUB DAS BANYU IRANG DAS MALUKA - Norsaidah Norsaidah; Muhammad Ruslan; Syarifuddin Kadir (Jurnal Sylva Scienteae, 2021)
The purpose of this study was to analyze the level of land criticality in the Banyu Irang Sub-watershed in the Maluka Watershed and determine the direction of forest and land rehabilitation based on the level of land criticality in the Banyu Irang Watershed in the Maluka Watershed. The method used is purposive sampling with observation points determined through the overlay of land cover maps, slope maps and soil type maps. Critical Land Analysis in the area of agricultural forest cultivation using productivity factors, slope factors, erosion factors or TBE (Erosion Hazard Levels) and management factors. The results on forest land cover are critical level of critical land, shrub land critical level critical to very critical, reeds critical land level critical and plantation level critical land critical potential to somewhat criticalTujuan dari penelitian ini untuk menganalisis tingkat kekritisan lahan di Sub DAS Banyu Irang DAS Maluka dan menentukan arahan rehabilitasi hutan dan lahan berdasarkan tingkat kekritisan lahan di Sub DAS Banyu Irang DAS Maluka. Metode yang digunakan adalah purposive sampling dengan titik pengamatan yang ditetapkan melalui hasil overlay peta penutupan lahan, peta kelerengan dan peta jenis tanah. Analisis Lahan Kritis pada kawasan hutan budidaya pertanian menggunakan faktor produktivitas, faktor kemiringan lereng, faktor erosi atau TBE (Tingkat Bahaya Erosi) dan faktor manajemen. Hasil pada penutupan lahan hutan tingkat kekritisan lahannya agak kritis, semak belukar tingkat kekritisan lahannya kritis sampai sangat kritis, alang-alang tingkat kekritisan lahannya kritis dan perkebunan tingkat kekritisan lahannya potensial kritis sampai agak kritis